2008
DOI: 10.1086/526426
|View full text |Cite|
|
Sign up to set email alerts
|

First Catalog of Strong Lens Candidates in the COSMOS Field

Abstract: We present the first catalog of 67 strong galaxy-galaxy lens candidates discovered in the 1.64 deg 2 Hubble Space Telescope COSMOS survey. Twenty of these systems display multiple images or strongly curved large arcs. Our initial search is performed by visual inspection of the data and is restricted, for practical considerations, to massive early-type lens galaxies with arcs found at radii smaller than $5 00 . Simple mass models are constructed for the best lens candidates, and our results are compared to the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(50 citation statements)
references
References 63 publications
(69 reference statements)
1
48
0
1
Order By: Relevance
“…These equations were applied to five bona fide gravitational rings taken from the recent COSMOS survey [15] and the results are given in Table 3. As in the precedent case, corrections due to the cosmological constant on the mass values are of the order of 2%.…”
Section: The Effect Of λ On Mass Estimatesmentioning
confidence: 99%
“…These equations were applied to five bona fide gravitational rings taken from the recent COSMOS survey [15] and the results are given in Table 3. As in the precedent case, corrections due to the cosmological constant on the mass values are of the order of 2%.…”
Section: The Effect Of λ On Mass Estimatesmentioning
confidence: 99%
“…The largest homogeneously-selected sample of confirmed strong lenses is the Sloan Lens ACS Survey (SLACS; Bolton et al 2006Bolton et al , 2008, which yielded more than a hundred spectroscopically confirmed strong lenses with complete redshift information and high-resolution imaging follow-up (with e.g., the Hubble Space Telescope and Keck Observatory Adaptive Optics). In total, all lens surveys combined have produced up to a thousand highly-likely 2 gravitational lens candidates (e.g., Browne et al 2003;Faure et al 2008;Treu et al 2011;Inada et al 2012;Brownstein et al 2012;More et al 2012;Stark et al 2013;Sonnenfeld et al 2013a;Gavazzi et al 2014;More et al 2016;Shu et al 2016Shu et al , 2017.…”
Section: Introductionmentioning
confidence: 99%
“…Systems with references are previously known, whereas other objects with "..." are new. References: 1 2016), 9 Cabanac et al (2007), 10 Stark et al (2013), 11 Tanaka et al (2016), 12 Bolton et al (2008), 13 Faure et al (2008), 14 Hammer (1991), 15 Carrasco et al (2017), 16 Chan et al (2019), 17 Tyson et al (1990). acquired through three arms, the ultraviolet (UVB, λλ3,000 -5,500 Å), the visual (VIS, λλ5,000 -10,500 Å), and the near-infrared (NIR, λλ10,000 -25,000 Å).…”
Section: Spectroscopic Follow-upmentioning
confidence: 99%